Merawat Nusantara: Kontemplasi Atas Kisah Kaum Saba’ Dalam Kitab Suci Umat Islam - Hawari, Nadirsah; Arifin, Arifin; Thoriq, A Yuda Ath; Rahma, Fina Afifatur; Ramadhan, Syahril; Saputri, Yelvi Mai Tano (AL-ADYAN, 2019)
This paper tries to explore a noble lesson from a life journey of a nation that has experienced glory in managing their lives at that time. The Saba 'with all the stories we can read from the source of the holy book and the explanations of the commentators in it so that their stories continue to be the talk of the last generation, especially when we live in an era of fast-paced, sophisticated and technology-based and information. IT sophistication and human greatness when combined should give birth to a mighty power that can change the arid world order to be fertile, weak to strong, hard to be easy even poor to become rich. But the empirical facts are not so. What's wrong with us and can we learn from the story of the people in the past? The main problem in this study is the extent of the triumph and the key to the success of the rulers of the country of Saba 'in prospering its people and what is the main cause of their destruction. This study is descriptive analytic with reference to the interpretations and explanations of the commentators in telling the story of the Sabaese '. Wal results that the Saba''is an order of community life that had achieved the glory and success in managing the favors of power ruled by its ruler at the time, but because of kufr and their inability to control their desires finally they sank and fell from the stage of civilization. For millennials, stories of the failure of the people in the past should be a lesson for the current generation so that the goodness of the earth and all its contents are not wasted.